2021
DOI: 10.1088/1361-6501/ac04e1
|View full text |Cite
|
Sign up to set email alerts
|

A method of fine size measurement for telecentricity-based error compensation

Abstract: Focusing on the stable magnification, near zero distortion, and wide field of depth (DoF), the telecentric optical system is well suited for size measurements with a large range of working distances. However, suffering from the telecentricity-based error (TBE), the size measurement is connected with the working distances and imaging position of the image sensor, even within the DoF. Therefore, a model of TBE compensation is established, inspired by the radial distortion model in the camera calibration. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Optical methods predominantly depend on the disk encoder scheme, commonly denoting the grating encoder arrangement, which employs a grating disk configuration for measurement purposes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Previous researchers have conducted a lot of research on it, including structural optimization [ 36 ] and algorithm supplementary modifications [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The above method mainly relies on the scale of the code disk to measure large angles.…”
Section: High-precision With Single Axismentioning
confidence: 99%
“…Optical methods predominantly depend on the disk encoder scheme, commonly denoting the grating encoder arrangement, which employs a grating disk configuration for measurement purposes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Previous researchers have conducted a lot of research on it, including structural optimization [ 36 ] and algorithm supplementary modifications [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The above method mainly relies on the scale of the code disk to measure large angles.…”
Section: High-precision With Single Axismentioning
confidence: 99%
“…Zhang et al [18] proposed a self-calibration method for circular encoders with multiple reading heads, deduced and analyzed the principle of error suppression of the reading head layout on the calibration results through harmonic analysis of angle measurement errors, and established a nonuniformly distributed layout of the reading heads to eliminate higher-order harmonic errors. Li et al [19] introduced the main sources of error in angle measurements of circular encoders, analyzed the distribution pattern of angle measurement errors, and calibrated the accuracy of angle measurement using higher precision instruments. Additionally, the calibrated error data were fitted into a third-order sine function for error correction, and the effectiveness of the error correction was verified through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…With this feature, telecentric imaging systems have been widely used to machine vision applications, including form error evaluation, geometry recognition, 3D reconstruction, etc [17,18]. In addition, research has suggested the possibility of applying telecentric imaging techniques to algebraic geometric forms [19]. When it comes to camera selection, line scan cameras offer four main advantages compared to area scan cameras: higher resolution, faster acquisition speed, continuous acquisition and processing, and a simple and reasonable structure.…”
Section: Introductionmentioning
confidence: 99%